Adenoid cystic carcinoma of palate: A case report and review of literature - Naga Sirisha Venkata Chundru; Rajesh Amudala; Prasanth Thankappan; Chandan Dasa Nagaraju (Wolters Kluwer Medknow Publications, 2013)
Adenoid cystic carcinoma is an uncommon, slow growing malignant salivary gland tumor that is characterized by wide local infiltration, perineural spread, propensity to local recurrence and distant metastasis. In this paper, the authors present a case of adenoid cystic carcinoma affecting the palate and involving the maxillary sinus in a 60-year-old male patient along with a brief review of literature.